Community Empowerment Strategy of Pondok Agung, Kasembon Sub-district through Biogas Technology to Reduce Cattle Waste Pollution in Water - Maimunah, Yunita; Kilawati, Yuni; Muttaqin, Adharul; Amrillah, Attabik Mukhammad; Kartikasari, Dany Primanita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The community-based biogas project in Kasembon sub-district focuses on utilising livestock manure as a renewable energy source and organic fertiliser producer to improve community welfare and reduce negative environmental impacts. Through an Asset-Based Community Development (ABCD) approach, the project identifies local assets, such as land and manure, and empowers the local community to maintain the biogas system. The biogas production process produces environmentally friendly energy and reduces dependence on LPG. In addition, the organic fertiliser made from biogas waste can be utilised in agriculture to improve productivity and soil health. The implementation of ABCD encourages collaboration between the community, government, and university, and creates new economic opportunities by selling organic fertiliser. However, challenges such as dependence on external assistance, high initial capital requirements, and technical limitations hinder long-term sustainability.